2021
DOI: 10.3389/fbioe.2020.622186
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Proteins 90 kDa: Immunomodulators and Adjuvants in Vaccine Design Against Infectious Diseases

Abstract: Heat shock proteins 90 kDa (Hsp90s) were originally identified as stress-responsive proteins and described to participate in several homeostatic processes. Additionally, extracellular Hsp90s have the ability to bind to surface receptors and activate cellular functions related to immune response (cytokine secretion, cell maturation, and antigen presentation), making them very attractive to be studied as immunomodulators. In this context, Hsp90s are proposed as new adjuvants in the design of novel vaccine formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 119 publications
(279 reference statements)
1
13
0
Order By: Relevance
“…HSP 90 kDa (Hsp90) is one of the typical proteins which protect against thermal damage, and it can bind to surface receptors and activate cellular functions related to immune response upon thermal injuries. 52 The Hsp90 expression is significantly upregulated in both the mPDA and CO@mPDA groups when compared with that by the PBS group (Fig. 7A–C), which suggests it has a spontaneously protective effect against thermal injuries in tissues.…”
Section: Resultsmentioning
confidence: 86%
“…HSP 90 kDa (Hsp90) is one of the typical proteins which protect against thermal damage, and it can bind to surface receptors and activate cellular functions related to immune response upon thermal injuries. 52 The Hsp90 expression is significantly upregulated in both the mPDA and CO@mPDA groups when compared with that by the PBS group (Fig. 7A–C), which suggests it has a spontaneously protective effect against thermal injuries in tissues.…”
Section: Resultsmentioning
confidence: 86%
“…In this study, we focused on a commercial lipid reagent (lipofectamine) along with a physical method (heat shock under various conditions) for gene transfer in four mammalian cell lines with the same tissue origin (epithelial tissue). Several studies indicated the importance of heat shock proteins such as Hsp90, Hsp70 and Gp96 as an adjuvant for enhancement of humoral and cellular immune responses against infections (Corigliano et al 2021 ; Dalimi and Nasiri 2020 ; Gupta et al 2020 ). Our previous study showed that Hsp27 could be used as a vaccine adjuvant to enhance HIV-1 Nef antigen-specific immunity in DNA-based immunization (Milani et al 2017a ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, efforts have been made to increase vaccine immunogenicity through the integration of appropriate adjuvants, specific antigen targeting and effective carriers. Innovative approaches are imperative in the quest to create non-toxic adjuvants and less immunogenic delivery carriers for treatment of various infectious diseases [1,2]. In recent years, there has been a significant focus on continuous pre-clinical and clinical trials aimed at creating an efficacious HIV vaccine.…”
Section: Introductionmentioning
confidence: 99%